Perceived stress and coping strategies among undergraduate nursing students in the psychiatric practicum during the COVID-19 pandemic: A cross-sectional quantitative study - Shiou-Fang Lu; Shu-Wan Chiang; Ya-Chuan Hsu (Tzu Chi Medical Journal)
Objectives: This study aimed to explore perceived stress and coping strategies among undergraduate nursing students in the psychiatric practicum during the pandemic. Materials and Methods: A cross-sectional quantitative design was employed in this study. Data were collected through self-administered questionnaires consisting of demographic variables, the Perceived Stress Scale (PSS), and the Coping Behavior Inventory (CBI). Results: Of the 73 participants, 82.2% were women. The mean age was 21.25 ± 0.69 years. The overall mean score of PSS was 1.45 ± 0.48, and that of CBI was 1.93 ± 0.31. The major sources of perceived stress were taking care of patients (1.72 ± 0.54) and assignments and workload (1.72 ± 0.75). The major coping strategies to deal with stress were problem-solving (2.66 ± 0.52) and staying optimistic (2.43 ± 0.73). Pearson’s correlation analyses revealed that participants who utilized the avoidance strategy (r = 0.416) reported high-stress levels, whereas participants who utilized problem-solving (r = −0.306) and staying optimistic (r = −0.527) reported low-stress levels. Conclusion: The nursing students perceived moderate stress mainly from taking care of patients as well as assignments and workload. Problem-solving and staying optimistic were the most frequently used coping strategies. Compared with findings from other studies, our data suggested that the impact of the COVID-19 pandemic on perceived stress was not apparent possibly due to well-established approaches and education for infection prevention and control in our hospitals and schools. Our findings may provide valuable information to maximize students’ learning opportunities.